Journaling program development as an effort to improve student literacy skills - Widya Harefaningtyas (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The phenomenon of the low literacy level of elementary school students that occurs at UPTD SDN 3 Kerticala has an impact on students' common writing and reading skills. One alternative way that can be done to improve literacy skills in students, especially writing skills, is with a journaling training program. The type of research the author uses is qualitative research with descriptive methods. The subject of implementing this journaling program is class IV with 9 students. The procedure used in this study is the action class, which consists of 4 stages: (1) planning, (2) implementation of the action, (3) observance or observation, and (4) reflection. There were still deficiencies in the research conducted, as this research was not very in-depth and only carried out once. Hence, the results could have been more optimal, and there were no significant results from implementing programs designed to improve students' literacy skills at UPTD SDN 3 Kerticala. This limitation is expected to be a reference for improvement and further program development.   Abstrak Fenomena rendahnya tingkat literasi siswa sekolah dasar yang terjadi di UPTD SDN 3 Kerticala berdampak pada kurangnya kemampuan menulis dan membaca pada siswa. Salah satu alternatif cara yang dapat dilakukan untuk meningkatkan kemampuan literasi pada siswa, terutama keterampilan menulis, yaitu dengan pembinaan program journaling. Jenis penelitian yang digunakan penulis adalah penelitian kualitatif dengan metode deskriptif. Subjek penerapan program journaling ini, yaitu kelas IV dengan jumlah 9 siswa. Prosedur yang digunakan dalam penelitian ini, yaitu tindakan kelas yang terdiri dari 4 tahap, di antaranya (1) perencanaan, (2) pelaksanaan tindakan, (3) pengamatan atau observasi, dan (4) refleksi. Pada penelitian yang dilakukan masih terdapat kekurangan, seperti halnya penelitian ini belum terlalu mendalam dan hanya dilaksanakan sekali sehingga hasilnya tidak maksimal dan belum terlihat hasil yang signifikan dari penerapan program yang dibuat untuk peningkatan kemampuan literasi siswa di UPTD SDN 3 Kerticala. Adanya keterbatasan ini, diharapkan dapat menjadi acuan perbaikan dan pengembangan program selanjutnya. Kata Kunci: Kemampuan literasi; keterampilan menulis; journaling